2015
DOI: 10.1099/mic.0.000024
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial toxin colicin N and phage protein G3p compete with TolB for a binding site on TolA

Abstract: Most colicins kill Escherichia coli cells by membrane pore formation or nuclease activity and, superficially, the mechanisms are similar: receptor binding, translocon recruitment, periplasmic receptor binding and membrane insertion. However, in detail, they employ a wide variety of molecular interactions that reveal a high degree of evolutionary diversification. Group A colicins bind to members of the TolQRAB complex in the periplasm and heterotrimeric complexes of colicin–TolA–TolB have been observed for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
(143 reference statements)
3
13
0
Order By: Relevance
“…RcsF functions in the signal transduction from the cell surface to Rcs signaling system (Castanie-Cornet et al, 2006;Sato et al, 2017), while OmpA, which acts as an outer membrane (OM) porin, can form channels through the cellular membranes (Hong et al, 2006). TolB plays a role in OM invagination during cell constriction in the trans-envelope Tol-pal system (Zhuang et al, 2002;Gerding et al, 2007;Ridley and Lakey, 2015). The Fts opera, containing FtsA, FtsI, FtsL, and FtsQ, are involved in cell division (Chen and Beckwith, 2001;Kureisaite-Ciziene et al, 2018;Du et al, 2019).…”
Section: Bioinformatics Analysis On the Cell Division And Cell Wall Bmentioning
confidence: 99%
“…RcsF functions in the signal transduction from the cell surface to Rcs signaling system (Castanie-Cornet et al, 2006;Sato et al, 2017), while OmpA, which acts as an outer membrane (OM) porin, can form channels through the cellular membranes (Hong et al, 2006). TolB plays a role in OM invagination during cell constriction in the trans-envelope Tol-pal system (Zhuang et al, 2002;Gerding et al, 2007;Ridley and Lakey, 2015). The Fts opera, containing FtsA, FtsI, FtsL, and FtsQ, are involved in cell division (Chen and Beckwith, 2001;Kureisaite-Ciziene et al, 2018;Du et al, 2019).…”
Section: Bioinformatics Analysis On the Cell Division And Cell Wall Bmentioning
confidence: 99%
“…First, point mutations or deletions in tolA differentially affect colicin import; some remain active, whereas others lose their ability to kill mutated strains (59,89). Second, structural data have shown that the colicin A T-domain interacts with the convex site of TolAIII, whereas the phage Ff and IF1 pIII-N1 domain and colicin N T-domain bind to the concave side of TolAIII (18,21,(90)(91)(92)(93) (Fig. 1B).…”
Section: The Tol System Serves As a Versatile Import Machinery For Pamentioning
confidence: 99%
“…The colicins produced by some isolates of E.coli are effective against many species of Gram negative and some Gram positive bacteria [31]. The agreement study was reported that the colicin had the ability of inhibiting the growth of one or more species and/or strains of pathogenic Enterobacteriaceae [32].…”
Section: Wavelengt H Abmentioning
confidence: 99%